Legal: Use of Force in Self-Defence to Recover Occupied Territory. (28th January 2022) - Akande, Dapo; Tzanakopoulos, Antonios
Abstract: This article argues that, in certain circumstances, it is legal for a state to use force in self-defence in order to recover territory unlawfully occupied by another state as a result of an armed attack. Where occupation follows from an unlawful armed attack, the occupation is a continuing armed attack, and the attacked state does not lose its right to self-defence simply because of passage of time. It is argued that while it is trite law that territorial disputes cannot be resolved by recourse to force, it is important to draw the distinction between a territorial dispute, on the one hand, and a situation of armed attack resulting in occupation of territory, on the other. Furthermore, where years pass between the initial attack and the use of force in self-defence, that may suggest that there is no other reasonable means of bringing the armed attack and occupation to an end, rendering the use of force in self-defence the ultima ratio – which is precisely the point of the necessity requirement. On this view, time runs against, rather than in favour of, the aggressor.